EFFECT OF CHLORINE GAS DERIVED FROM SALT WATER ELECTROLYSIS ON THE DECREASE OF AIR MICROBE NUMBER OF HOSPITAL CARE-ROOMS (NOSOCOMIAL INFECTIONS PREVENTION THROUGH THE CONTROL OF AIR MICROBE POLLUTION) - Ganefati, Sri Puji (International Journal of Psychosocial Rehabilitation, 2020)
Nosocomial infection is a new disease in patients who are treated for 48 hours. Cases of 40% nosocomial infection are caused by Staphylococcus aureus and 50% gram-negative microorganisms. This case is the main cause of patientsdeath in the hospital. Control efforts through disinfection of hospital care-rooms with Cl2 gas from salt water electrolysis. The purpose of this study was to determine: the effect of Cl2 gas on decreasing microbe number; the influence of salt levels on the decrease in the microbe number and electrolyzers which most reduced the micorbe number in the hospital care-rooms.This research was Quasi Experiment (quantitative) with Pre Test and Post Test Group Design. Location is determined by quota sampling. The population of the study was 42 rooms, 32 rooms sample, Stratified Random Sampling technique, and calculation used the Slovin formula.The results showed that there was an effect of chlorine gas (Cl2) from salt water electrolysis ondecrease in microbe number, there was an influence of ferocious levels on the decrease in microbe number, and Cl2 of the 13 voltage electrolyzer with a salt content of 200 gr/L reduced the mostmicrobe number.There are effectedthe various electrolyzer models on decreasedto the number of germs which mean that there was an influence of electrolyzer voltage variations and salt content on decreasing bacterial numbers.